Potential of Taman Tamadun Islam as an attraction tourism centre at Kuala Terengganu / Che Ahmad Rahiman Che Rozaid - Che Rozaid, Che Ahmad Rahiman (Universiti Teknologi Mara, Perak, 2021)
Taman Tamadun Islam was one of the attractions and tourism centre in Kuala Terengganu. It has a big potential and attraction to convince tourist and local people to visit this tourism centre. Based on visitor’s arrival graph from Rancangan Tempatan Daerah Kuala Terengganu 2035. Shown that its decreasing drastically which means this tourism centre is getting losing visitors year by year. It was the bad thing that could give a negative effect to tourism industry and economy in Kuala Terengganu. Based on the preliminary study from the secondary sources, one of the causes that was leading to this lack of tourists stems from the physical elements of attraction such as lack of tourism attraction’s elements, tourism attraction’s elements is not well cared and maintained, bad effect on the economy, location of this tourism centre, Lack of landscape such as softscape and hardscape elements, hardscape elements not well maintained, lack of food, shop and souvenir stalls that conducting day and night business activities and etc. The objectives of this study in order to achieve the aim was to identify the existing attraction and tourism elements at Taman Tamadun Islam, to analyse the issues of existing attraction and tourism elements at Taman Tamadun Islam and to analyse the potential of existing attraction and tourism elements at Taman Tamadun Islam. This research is based on data obtained from a distribution analysis, statistical analysis and questionnaire’s survey that reviews the community’s opinion and response towards the tourism issues of Taman Tamadun Islam. Analysed data collected based on the needs of community will be given priority in this effort to restore and improve the tourism attraction and economy in Kuala Terengganu.